Будівлі з нішоподібними печами у господарстві давніх слов’ян (за матеріалами Пересопниці, уроч. Пастівник) - Прищепа, Б.А.; Горбаненко, С.А. (Археологія, 2016)
У статті здійснено повну публікацію будівель незначних розмірів із нішоподібними печами з ранньослов’янського поселення в уроч. Пастівник на Пересопниці. Розглянуто аналогічні будівлі, що знаходяться переважно на Волині. Зроблено висновки, що більшість таких будівель є спеціальними спорудами для приготування їжі. The article presents a comprehensive publication of small size structures with bay-shaped stoves from the excavations at the Early Slavs’ settlement in Pastivnyk Tract in Peresopnytsia of the Rivne Region and Oblast. There are three of them studied since 2002 during the period of active research: No 1 in excavation area 1, No 2 in excavation area 8, and No 1 in excavation area 9. There was the other stove to the left from the last mentioned. Based on the filling in the foundation pits, the structures are dated by the 10th century. Finds in the structures at Pastivnyk testify for their usage in work with «bread», or wider for cooking: fragments of millstones were found in structure 1/1; three types of various kitchen remains were found in No 2/8, and filling No 1/9 contained a significant admixture of burnt grains of cultivated cereals. The fact that such structures were not used as workshops (ceramic, ironworking, etc.) is indirectly evidenced by the planigraphy of the settlements: in cases where it was possible to trace, such structures were situated in immediate proximity to the dwellings, as well as in the residential area of the settlements. A review of similar structures is made which are situated mainly in Volyn. It is probable that such tradition of farmstead organization, in which structures for cooking were settled separately and outside the dwelling room, was spread at a very limited local territory, was appropriate for the annalistic Volynians, and was their own distinctive tribal peculiarity of farmstead organization. В статье осуществлена полная публикация построек незначительных размеров с нишевидными печами из раскопок раннеславянского поселения в уроч. Пастивнык в Пересопнице (Ровненский р-н, Ровненская обл.) (рис. 1). За время активных исследований, с 2002 г. и по ныне, таких изучено три: № 1 в раскопе 1, № 2 в раскопе 8 и № 1 в раскопе 9. В последней была вторая печь слева от первой (рис. 2; 3). По материалам из заполнения котлованов (рис. 4), постройки датированы Х в. Находки в постройках из Пастивныка свидетельствуют в пользу их использования для работы с «хлебом», или обширнее — для приготовления еды. В постройке 1/1 обнаружены фрагменты жерновых камней, в № 2/8 — обнаружено три вида различных кухонных остатков, а заполнение № 1/9 содержало значительную примесь обгоревших зерновок культурных злаков. О том, что такие постройки не использовали в качестве мастерских (гончарных, железоделательных …), косвенно свидетельствует планиграфия поселений — там где это было возможно проследить, такие постройки располагались в непосредственной близости от жилищ, а также в жилой зоне поселений. Осуществлен обзор аналогичных построек, которые преимущественно находятся на Волыни (рис. 5). Не исключено, что такая традиция устройства хозяйства-двора, при которой отдельно обустраивали сооружение для приготовления пищи вне жилого помещения, была распространена на очень ограниченной, локальной территории, характерна именно летописным волынянам и была их определенной племенной особенностью устройства хозяйства-двора.